2009
DOI: 10.1155/2009/275613
|View full text |Cite
|
Sign up to set email alerts
|

Maternal History and Uterine Artery Doppler in the Assessment of Risk for Development of Early- and Late-Onset Preeclampsia and Intrauterine Growth Restriction

Abstract: Objective. To examine the value of one-step uterine artery Doppler at 20 weeks of gestation in the prediction pre-eclampsia (PE) and/or intrauterine growth restriction (IUGR). Methods. A prospective multicentre study that included all women with singleton pregnancies at 19–22 weeks of gestation (w). The mean pulsatility index (mPI) of both uterine arteries was calculated. Receiver-operating characteristics curves (ROC) were drawn to compare uterine artery Doppler and maternal risk factors for the prediction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
42
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 27 publications
9
42
0
1
Order By: Relevance
“…Concerning sFlt-1, although second- and third-trimester levels before the onset of PE have been consistently reported to be higher [11,16,21], findings in first-trimester patients are conflicting. Several studies reported similar sFlt-1 values between cases and controls, either when overall PE was used as main outcome measure [16,22,23,24,25,26] or when patients were grouped as early- and late-onset disease [27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Concerning sFlt-1, although second- and third-trimester levels before the onset of PE have been consistently reported to be higher [11,16,21], findings in first-trimester patients are conflicting. Several studies reported similar sFlt-1 values between cases and controls, either when overall PE was used as main outcome measure [16,22,23,24,25,26] or when patients were grouped as early- and late-onset disease [27].…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of algorithms based on baseline and biophysical factors has been reported to be lower in populations with low cardiovascular risk [9,11,20] in comparison with higher-risk pregnant populations. Angiogenic factors represent the most accurate maternal biomarkers characterizing the presence of PE, as they are a direct reflection of the pathophysiological placental and endothelial processes involved in the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar values have been obtained in some of the previous studies. [22][23][24] There was no association between uterine artery PI >95 th percentile and spontaneous preterm delivery in the present study. Similar results have been obtained in previous study.…”
Section: Discussionmentioning
confidence: 56%
“…We also found that HIF-1α and 8-OHdG staining in preeclamptic women with FGR was stronger than in preeclamptic women without FGR. 5,18,19) Furthermore, almost all preeclamptic women with FGR had early-onset preeclampsia, and almost all preeclamptic women without FGR had late-onset preeclampsia. The mean PI in early-onset preeclamptic women was significantly greater than in late-onset preeclamptic women.…”
Section: Discussionmentioning
confidence: 99%